Species of Herb Plants used as Traditional Medicine in the Home Gardens of The Aceh Tengah Community - Ernilasari Ernilasari; Yuslinaini Yuslinaini; Saudah Saudah; Rizky Ahadi (Universitas Serambi Mekkah, 2022)
The practice of using plants as medicine and using herbs in traditional medicinal ingredients has long been carried out by the people of Indonesia. The medical tradition of a community is influenced by knowledge about traditional medicine which is passed down from generation to generation, level of need, social culture, community education, as well as physical and ecological factors of the local area.This study aims to record the types of herbs plants used as medicine in the home gardens of Aceh Tengah community. This study uses observation and interview methods.Based on the research results, it was found that 24 species of herbs plants were used as medicine in the home gardens of the Aceh Tengah Community, which were grouped into 10 families.The most commonly found family is Zingiberaceae. Keywords: Herbs, Tradisional medice, Aceh Tengah